Legal Protection of Women Victims of Sexual Harassment on Campus in The Indonesian Criminal Justice System Reviewed from Permendikbud Number 30 of 2021 - Putra, Rizky Perdana Bayu; Masruchi, Zainal Arif; Doroh, Gasper; Irawan, Joni; Milka Kumala; Saputra, Moch Edy (International Journal of Sustainable Law, 2024)
This study aims to understand the form of legal protection in accordance with the latest policies related to the Prevention and Handling of Sexual Violence (PPKS) on campus in terms of Permendikbud No. 30 of 2021. Sexual harassment is a crime committed by harassing, humiliating, insulting which results in psychological or physical suffering. This sexual crime does not only occur in the private sphere, family environment, gaming environment, office and company environment. But it can also happen in the college environment. The formulation of the problem in this article is mainly whether victims of sexual harassment in the university environment can obtain legal protection. And second, how legal protection for victims of sexual harassment in higher education is reviewed from Permendikbud No. 30 of 2021. The research method used is normative legal research. With the presence of Permendikbud Edition 30 of 2021, there is no reason for universities not to prevent and overcome sexual violence. There are several types of sexual violence, namely psychological violence, physical violence, economic violence, verbal violence and cyber-sexual violence